2017
DOI: 10.3390/su9050770
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Productivity and Resource Conservation by Eliminating Inefficiency of Thai Rice Farmers: A Zero Inefficiency Stochastic Frontier Approach

Abstract: The study first identified fully efficient farmers and then estimated technical efficiency of inefficient farmers, identifying their determinants by applying a Zero Inefficiency Stochastic Frontier Model (ZISFM) on a sample of 300 rice farmers from central-northern Thailand. Next, the study developed scenarios of potential production increase and resource conservation if technical inefficiency was eliminated. Results revealed that 13% of the sampled farmers were fully efficient, thereby justifying the use of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…TE of an individual farm producer (Equation (2)) is defined as the ratio of the observed output (Y) to the corresponding frontier output (Y * ) [16]. The model is expressed as follows [21][22][23]:…”
Section: Methodsmentioning
confidence: 99%
“…TE of an individual farm producer (Equation (2)) is defined as the ratio of the observed output (Y) to the corresponding frontier output (Y * ) [16]. The model is expressed as follows [21][22][23]:…”
Section: Methodsmentioning
confidence: 99%
“…The farmers who achieved relatively higher education level are believed to have higher exposure to agricultural technology and agricultural technology adoption possibility. This could enhance the farm productivity per hectare, since better educated farmers are more likely to adopt modern equipment efficiently [11,25].…”
Section: Education Level Of the Household Head (Edu)mentioning
confidence: 99%
“…2 Typically, in the literature, two empirical approaches have been broadly used to estimate TE. The first is DEA, which is a nonparametric approach involving the use of linear programming techniques (Khataza et al 2019;Liu et al 2017). Although efficiency estimation using DEA does not impose a functional form on the data, this approach fails to effectively address statistical noise that is likely to affect the accuracy of estimates (Khataza et al 2019;Liu et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Gebremedhin et al (2009) also found that education has a significantly positive effect in improving the TE of smallholder farmers in Ethiopia. As a plausible explanation for this finding, better educated farmers are likely to have better access to necessary information on the state of agricultural technologies and on the optimal use of farming practices than their counterparts (Liu et al 2017).…”
Section: Determinants Of Technical Efficiencymentioning
confidence: 99%